Da maniva ao grolado: práticas produtivas e patrimoniais no processo identitário dos Tremembé de Almofala (CE) - Saldanha Neto, Canuto Diógenes (2014)
The indigenous political scene in Brazil is undergoing transformations that need to be better analyzed by scholars in the field of the Social Sciences. The deficit in the policy of indigenous land demarcation emerges as the largest obstacle in the conquest of collective rights. Therefore, a study to analyze renewed strategies in the struggle for social rights, and their implications in local everyday life relations, is urgent. In this context, the aim of this research is to understand the current social dynamics of identity among the Tremembé people of Almofala, in the state of Ceará, Brazil, with a fieldwork conducted in the flour mill of the Casa de Farinha Comunitária project, in the Lameirão community. Specific aims are: a) to analyze the processes involved in the project in order to comprehend their meanings and appropriations as well as their everyday life and political uses; b) understand the strategies to fight for social benefits; c) analyze the local ethnic classifications grounding the construction of the Tremembé identity in Almofala. Methods deployed are ethnography of communities, used to apprehend the social production of networks of relationships, and a social cartography of practices. The realization of rights demanded by the indigenous populations in Brazil is intertwined with a process of social and legal legitimation their identity and cultural heritage. Such legitimation works as a safeguard mechanism of rights secured by the Constitution. Therefore, to own a “cultural heritage” is perceived as a “passport” to benefit from emerging rights. Amid this context, changes in the traditional processing of the cassava root, a productive practice shared locally by diverse social groups, is reified as cultural heritage by the Tremembé people of Almofala and their network of collaborators in the pursuit of accessing distinctive public policies. Furthermore, the research came across specific social arrangements of local subjects which unfolded internal struggles, enabling to understand the dynamics of the Tremembé of Almofala identity process.